THE EFFECT OF IMPLEMENTATION OF JIGSAW COOPERATIVE LEARNING MODEL ON THE STUDENT MATHEMATICS LEARNING OUTCOMES SD NEGERI 133 BONTOTIRO - Eman Wahyudi Kasim (IAIN Ambon, 2021)
The purpose of this study was to determine the effect of the implementation of the jigsaw cooperative learning model on the mathematics learning outcomes of elementary school students in SD Negeri 133 Bontotiro. This study uses an experimental approach with an experimental design of Pretest-Posttest Noneequivalent Group with data collection techniques through learning outcomes tests and teacher and student observation sheets. The data analysis technique in this research is descriptive analysis and inferential analysis which consists of normality test, homogeneity test and hypothesis testing. Based on the results of the research and discussion, it can be said that the implementation of the Jigsaw cooperative learning model on students at SDN 133 Bontotiro District is in the high category. Students' mathematics learning outcomes at SDN 133 Bontotiro District before the implementation of the Jigsaw Cooperative learning model obtained an average score of 34 and the learning outcomes after the implementation of the Jigsaw Cooperative learning model obtained an average score of 70 from the ideal score of 100. There is a positive influence from the implementation of the model Jigsaw cooperative learning to students' mathematics learning outcomes at SD 133 Bontotiro. The results of this study also show that the implementation of the Jigsaw cooperative learning model can be applied to improve student learning outcomes, especially in mathematics in elementary schools. Keywords: Jigsaw Type Cooperative Learning, Student Mathematics Learning Outcomes